2005
DOI: 10.1128/jb.187.18.6309-6316.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate Cyclase Mutations Rescue the degP Temperature-Sensitive Phenotype and Induce the Sigma E and Cpx Extracytoplasmic Stress Regulons in Escherichia coli

Abstract: Inactivation of the gene encoding the periplasmic protease DegP confers a high-temperature-sensitive phenotype in Escherichia coli. We have previously demonstrated that a degP mutant of E. coli strain CBM (W3110 pldA1) is not temperature sensitive and showed that this was most likely due to constitutive activation of the sigma E and Cpx extracytoplasmic stress regulons in the parent strain. In this study, further characterization of this strain revealed a previously unknown cryptic mutation that rescued the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The observation that a Δ cyaA strain displayed high levels of MicA even in exponential phase (Figure 2) was initially puzzling. Recently, however, it was found that the absence of cAMP results in strong induction of σ E activity (31); the mechanism by which this occurs is as yet unknown. Since the MicA-inducing stresses (in Figure 1) as well as stationary-phase growth have previously been associated with an increase in synthesis and/or activity of the ECF σ E (16,32), this factor is strongly suggested to be involved in micA regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that a Δ cyaA strain displayed high levels of MicA even in exponential phase (Figure 2) was initially puzzling. Recently, however, it was found that the absence of cAMP results in strong induction of σ E activity (31); the mechanism by which this occurs is as yet unknown. Since the MicA-inducing stresses (in Figure 1) as well as stationary-phase growth have previously been associated with an increase in synthesis and/or activity of the ECF σ E (16,32), this factor is strongly suggested to be involved in micA regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thermotolerance was examined using a modified protocol from Strozen et al (24). Cultures were diluted 1:1,000 and grown at 30°C in LB for 1 h. The cultures then were aliquoted into a 96-well microtiter plate (Costar) and incubated at 42°C using an Optima microplate reader (BMG Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…When phosphorylated by CpxA, CpxR-P acts as a transcriptional factor to activate or repress Ͼ100 gene targets in Escherichia coli (17). Several inducing cues are known, including elevated pH (13,53); adenylate cyclase mutations (79); depletion of phosphatidylethanolamine (48) or outer membrane phospholipase A (PldA) (42); and the accumulation of enterobacterial common antigen lipid II biosynthetic intermediate (14), assembly intermediates of pili (41), type IV secretion systems (90), and the outer membrane lipoprotein NlpE (78). All of these characteristics were seen with the Cpx system of E. coli, and they probably cause inappropriate protein folding in the periplasm.…”
mentioning
confidence: 99%